Design, characterisation and performance evaluation of a Peltier-driven cryo-adhesive fixture for manufacturing operations. (5th March 2018) - O'Shaughnessy, S.M.; Sloane, A.; Kearns, A.; Byrne, G.; Trimble, D.; O'Donnell, G.E.
Abstract: Workholding and fixturing is a critically important aspect of manufacturing that has direct implications for the quality of the manufactured component during processing as well as a direct impact on the cost of the component. The field of workholding is mature with numerous techniques employed, mostly using contact pressure, but also using magnetics and adhesives. Looking to nature for inspiration presents us with the use of ice as a mechanism for adhesion, referred to as cryo-adhesion. Cryo-adhesion offers some advantages over more traditional fixturing methods such as removing contact pressure and therefore reducing the dependence on the machining of complex, intricate bespoke fixtures. While the concept of ice adhesion is known, there is minimal research presented on the application of ice adhesion in manufacturing processes. This research reports on the development of a novel Peltier-based cryo-cooling fixture for workholding in manufacturing operations. The research provides insight into the main interactions that might be experienced in manufacturing type scenarios and presents findings on the cryo fixture's thermal and geometric characteristics, the use of the novel cryo fixture for holding various materials under tensile and shear loads, and a consideration of contact area and surface roughness on the cryo fixture performance. Graphical abstract: Image 1 Highlights: Peltier modules are successfully used to create a novel workpiece fixturing system based on ice adhesion. The cryo fixture creates a 9000 mm 2 'cold zone', and is shown to be capable of lowering the surface temperature to −17°C. Mechanical characterisation shows that workpiece adhesion strength initially increases with decreasing surface temperature. The adhesive strength increases with increasing workpiece contact area under both tensile and shear applied forces.